1981
DOI: 10.1161/01.cir.63.3.592
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function during sudden strenuous exercise.

Abstract: SUMMARY Strenuous exercise without warm-up has been shown to produce ischemia-like electrocardiographic (ECG) abnormalities in 60-70% of healthy subjects. These abnormalities appeared to be related to the development of an unfavorable myocardial supply/demand balance and, in chronically instruanented dogs, to transient decreases in coronary blood flow. A mechanism involving subendocardial ischemia has been proposed to explain the response to sudden strenuous exercise (SSE). To determine whether the response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Several previous studies on the effect of sudden strenuous exercise have been shown to produce ischemia-like ECG abnormalities in young healthy subjects during sudden strenuous exercise without warm-up [12,13]. Others [2] have reported normal ECG during sudden strenuous exercise following a warm-up.…”
Section: Discussionmentioning
confidence: 94%
“…Several previous studies on the effect of sudden strenuous exercise have been shown to produce ischemia-like ECG abnormalities in young healthy subjects during sudden strenuous exercise without warm-up [12,13]. Others [2] have reported normal ECG during sudden strenuous exercise following a warm-up.…”
Section: Discussionmentioning
confidence: 94%
“…The technique has been described previously [10,13]. Left ventricular ejection fraction was calculated from the backgroundcorrected lime activity curve as;…”
Section: Methodsmentioning
confidence: 99%
“…Functional capacity of end-stage renal disease (ESRD) patients is dramatically impaired, with changes occurring mainly in the cardiopulmonary and skeletal muscles, thus reducing maximum exercise tolerance [1,2]. Maximal oxygen uptake according to the Fick equation depends on the differential relationship between oxygen delivery (cardiac output and hemoglobin) and arteriovenous oxygen (av) O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Maximal oxygen uptake according to the Fick equation depends on the differential relationship between oxygen delivery (cardiac output and hemoglobin) and arteriovenous oxygen (av) O 2 . Therefore, an imbalance between oxygen demand-supply during exercise may expose ESRD patients to a low pH, which may alter left ventricular contractility and function [3,4] and in turn, reduce oxygen delivery to the working muscles [2].…”
Section: Introductionmentioning
confidence: 99%